Natural dyes extracted from Catharanthus flower petals for dye-sensitized solar cells application - Senevirathna, H.M.C.U. (University of Jaffna, 2022)
Dye-Sensitized Solar Cells (DSSCs) are one of the most studied cost-efficient solar cells with commercially available Ru-based dyes as the photosensitizer[1]. There has been a considerable interest to utilise natural dyes due to being environmentally friendly and economically superior to the commercially available Ru-based dyes [2]. This study focuses on utilising natural dyes extracted from Catharanthus flower petals as a photosensitizer for fabricating TiO2 based DSSC. Fresh flower petals were washed with deionized water before drying them to make a powder sample. Dyes were then extracted by soaking the power with ethanol and DI-water. The UV-Visible spectroscopy study reveals the presence of Chlorophyll and Anthocyanin in the ethanol extract. However, no distinguished peaks were observed for the dye-coated TiO2 films due to the interference of the TiO2 absorbance. Moreover, the uniform distribution of the dye molecules in the dye-coated TiO2 films was confirmed by the AFM study. DSSCs were then fabricated by doctor-blade method with the effective area of 0.25 cm2 utilising natural dye, 𝐼 − / 𝐼3 − redox couple and Pt electrode as a sensitizer, electrolyte and counter electrode, respectively. Finally, the photovoltaic performance of the fabricated devices was investigated under simulated irradiation of intensity 100 mW/cm2 with AM 1.5 filter. The device with ethanol extract of Catharanthus flower sensitized photoanode pronounced photovoltaic properties with short circuit current density, open circuit voltage and fill factor, 0.39 mAcm-2 , 0.56 V and 0.50, respectively.
Keywords: DSSCs; Natural dye; Catharanthus; Solar cell; Photovoltaic